Analyzing student perception of teacher quality. - Pridgen, J. (The Young Researcher)
The current teacher shortage occurring across the United States in public high schools has led to the development of Alternative Certification Programs (ACPs). This study aims to analyze the difference in student perception between traditionally certified teachers and alternatively certified teachers in the state of Texas in terms of teaching practices, teacher preparation, and teaching attri- butes. In this mixed-method research paper, a 27-item questionnaire on a Likert scale was distrib- uted to students at Mabank High School in the 2018-2019 academic school year. The students had the option to evaluate their second period teacher, fourth period teacher, or both. The results of this paper suggest that alternatively certified teachers are not significantly different in their teaching practices from traditionally trained teachers based off of student perception. However, the student perceptions of alternatively certified teachers were poorer in comparison to student perception of traditionally certified teachers in regard to teacher preparation and teaching attributes.